تأثير عمق الحراثة والتسميد بالزنك في الصفات الإنتاجية لصنف القطن (حلب 90) (Latakia University Journal -Biological Sciences Series, 2019)
نفذ البحث خلال الموسمين الزراعيين 2008 و 2009 لدراسة تأثير أعماق ثلاثة للحراثة (35 . 25 . 0 ) سم عند ثلاثة مستويات من سماد كبريتات الزنك(ZnSO4 .7H2O)  هي (50 . 25 . 0) كغ/هـ والتداخل بينهما على مكونات المحصول وإنتاجية القطن, أظهرت الدراسة النتائج الآتية: 1- حقق عمقي الحراثة زيادة معنوية في الخصائص الإنتاجية المدروسة مقارنة بعدم الحراثة من حيث طول الساق/سم خلال مرحلة النضج, وعدد الفروع الثمرية/النبات خلال مرحلة النضج, ومساحة المسطح الورقي خلال مرحلة أوج الإزهار, وعدد الجوزات/النبات, و وزن الجوزة, والإنتاج من القطن المحبوب. 2- حقق عمق الحراثة 35 سم زيادة معنوية في جميع الخواص المدروسة باستثناء عدد الجوزات / النبات بالمقارنة مع العمق 25 سم. 3- سبب التسميد بالزنك عند المعدل 50 كغ/هـ زيادة معنوية بالخصائص المذكورة أعلاه مقارنة بعدم الإضافة, وكذلك مقارنة بالمعدل 25 كغ/هـ, كما حقق المعدل 25 كغ/هـ زيادة معنوية بالخصائص المذكورة أعلاه مقارنة بعدم الإضافة. 4- أعطى التداخل بين عاملي التجربة تأثيرا" معنويا" في كافة الصفات المدروسة وخاصة الحراثة على عمق 35 سم والتسميد بمعدل 50 كغ/هـ. ووصلت الإنتاجية من القطن المحبوب إلى 6171.915 كغ/هـ كمتوسط لعامي البحث.The research work was  was carried out during the growing seasons of  2008 and 2009 to study effect of three tillage depths, viz. 0, 25 and 35 cm and three levels of zinc sulfate (ZnSO4 .7 H2O), viz., 0 , 25 , 50 kg / ha along with interactive effect  between them on yield attributes and productivity of cotton crop. The study showed the following results: 1- the tow depths of tillage (25 and 35 cm) significantly increased the studied parameters of productivity, in terms of plant height (cm) and number of sympodial branches/plant at plant maturity stage, leaf area at flowering peak, number of bolls/plant, boll weight and seed cotton yield, as compared to no-tillage. 2 - The tillage depth of (35) cm gave significantly increase in all of the studied parameters, except number of bolls\plant, compared to the depth of 25 cm. 3- Zinc fertilization at 50 kg\ha significantly increased all the above  mentioned properties as compared to rest of the treatments. Similar trend was also observed for the rate 25kg\ha. 4-The interactive effect between the two factors of this experiment gave significant difference in all of the studied parameters. 5- Combination of the tillage depth of 35cm and the zinc fertilization at 50 kg\ha gave the highest seed cotton yield (6171.915) as on average of the two seasons of the study.